การใช้องค์ความรู้ท้องถิ่นเรื่องรถม้าลำปางในการจัดการเรียนการสอนศิลปะ - สมสรวย, นันทิยา; สมสรวย, ปัณณธร (Journal of Education Studies, Chulalongkorn University, 2019)
Lampang Province is well known for being a horse carriage town. Besides using horses are a mean for transportation, this is as well a symbol for tourism in which the local who have been practicing horse carriage as an occupation, have established an education center comprising of the horse training centers, horse farms, horse carriage factories. In addition, there is a group making horse carriage models as souvenirs for tourists. Thus, this is considered as an ideal place to learn distinctive characteristics of local arts. Contents related to Lampang’s horse carriage can be used to develop visual arts stretching from the thinking process collected from horse carriage factories, the interview process of the local, the problem solving process of the horse carriage makers. These enable the learning process which underlines real situations and the historical art in the local areasupporting art and craft, traditional skills and local materials. Therefore, it is perceived as a tool sustaining local knowledge and to preserve differences across regions.